ISOLATION AND CHARACTERISATION OF SECONDARY METABOLITES FROM Dioclea reflexa (HOOK F.) AND Cussonia arborea (HOCHST) (2014)
The discovery of bioactive natural products is a basis for development of novel pharmaceuticals. Indigenous medicinal plants which are largely unexplored offer chemical diversity with structural complexity and biological potency. Despite their ethnomedicinal usage, there is little information on the bioactive components of Dioclea reflexa and Cussonia arborea. This study was designed to isolate and characterise the secondary metabolites from the roots of D. reflexa and C. arborea, and evaluate free radical scavenging activity of the isolates. One kilogramme each of authenticated D. reflexa root and C. arborea root-bark were collected from Eruwa, Oyo State. The air-dried samples of D. reflexa and C. arborea were purposively extracted with ethanol and methanol respectively. The crude extracts were separately fractionated on silica gel column chromatography with gradient elution using various solvents. The sub-fractions were further subjected to a combination of chromatographic techniques for isolation of pure compounds. Structures of isolated compounds were elucidated using one and two-dimensional Nuclear Magnetic Resonance (NMR), Infrared (IR), Ultra-Violet-Visible and Mass Spectroscopy (MS) techniques, and comparison with literature data for known compounds. The isolated compounds were evaluated for free radical scavenging potential in comparison with butylated hydroxyanisole following standard method. The ethanol extract (85 g) of D. reflexa on column chromatography gave β-sitosterol 1, lupeol 2, aurantiamide acetate 3, mearnsetin 6, 7,4′-dihydroxyflavone 7 and 3,5-dihydoxy-4-methoxybenzoic acid 8. The column yielded two new compounds, named lexaflavanone 4 and reflevone 5. Lexaflavanone showed the presence of sixteen carbons: 8C, 1CH2, 6CH and 1CH3. The MS gave M+ peak at m/z 302.0769 (Calcd. 302.0792), with 10 degree of unsaturation, corresponding to C16H14O6. The NMR signals were seen at δ 8.53, 7.70 (1H, d, J= 8.5 Hz), 6.58 (2H, s), 6.55 (1H, dd, J= 2, 8.5 Hz), 6.42 (1H, d, J= 2Hz), 5.36 (1H, dd, J= 2.5, 12.5 Hz), 2.93 (1H, dd, J= 12.5, 17 Hz, H-3axial) and 2.66 (1H, dd, J= 3, 17 Hz, H-3equi). The IR absorptions (υmax, cm-1) for OH (3361) C=O (1652) and C-C in ring (2917) were also detected. Reflevone, molecular formula C16H12O6 suggested δH signals: 6.54 (1H, s), 6.97(1H, dd), 7.02(1H, d) and 7.06 (2H, s), and δC signal: 177.9 (C=O) typical of flavone. In addition, its infra-red stretching absorptions (υmax, cm-1) revealed C-H sp2 (1570) and O-H (3377). The characteristics peaks of retro-Diels-Alder cleavage of ring C were observed in MS spectrum at m/z 137 and 166. Column chromatography of the methanol extract (18 g) of C. arborea yielded three known compounds, stigmasterol 9, oleanolic acid 10 and hederagenin 11 when compared with literature. The compounds were however new to the species of C. arborea. Lexaflavanone, reflevone and hederagenin exhibited free radical scavenging activity with IC50 of 58.14, 322.0 and 105.0 μM respectively. The plants have potentials for the development of drugs for the treatment of diseases with oxidative stress due to their free radical scavenging activities. Lexaflavanone and reflevone obtained from D. reflexa are new additions to the library of chemical compounds.